Effect types of coolant on tool wear and surface roughness - Loh, Choon Lee (2008)
Tool wear has been a critical issue in metal removal processes. In turning process, tool wear can create parts that are out-of-tolerance and eventually cause tool failure. The repetition of machining work that subjects on the tool tip interface to a range of cutting environments to comparatively evaluate their effect on tool life. The efficiency of cutting tools can be evaluated based on certain parameters such as flank wear, surface roughness on the work piece, cutting forces developed and temperature developed at the tool chip interface. The objective of this project is to determine the types of coolant influence on tool wear and surface roughness during turning of low-carbon steel AISI 1018, cold drawn, high temperature with carbide tool. Furthermore by using oil based coolant, water based coolant, and air as the coolant on the machining process, the three types of coolant are compared to evaluate the most effective coolant which resulting the less tool wear will be the optimum coolant. Next, we were used IM 7000 series Image Analyzer to observe and measure the tools wear microstructure occurs on the tool after the turning process by using different types of coolant. For surface roughness test, we were tested on surface texture of work pieces that have been machining using different types of coolant by using IM 7000 series PERTHOMETER. Then, the less surface roughness values were indicated the optimum coolant. Lastly, we were be resulting the optimum coolant that suitable use for the range of velocities from 400-600 m/min for material low-carbon steel AISI 1018, cold drawn, high temperature. The result indicated in general, oil based coolant performed better than other two coolants in reducing the tool wear and improving the surface finish. Oil based coolant has been used as one of the cutting fluids in this work because of its thermal and oxidative stability which is being comparable to other water based coolant and air used in the metal cutting industry.